A clue to the cause of acquired female sterility in fluffy mutant strains of Neurospora crassa. - S. Veenhuizen; H. G. Kolmark (Fungal Genetics Reports, 1986)
A clue to the cause of acquired female sterility in fluffy mutant strains of Neurospora crassa.